2021
DOI: 10.1155/2021/7596343
|View full text |Cite|
|
Sign up to set email alerts
|

N-Acetylcysteine (NAC) Inhibits Synthesis of IL-18 in Macrophage by Suppressing NLRP3 Expression to Reduce the Production of IFN-γ from NK Cells

Abstract: Background. N-Acetylcysteine (NAC) had exerted antioxidation and anti-inflammation effects on chronic obstructive pulmonary disease (COPD) patients. However, its effect in regulating interleukin- (IL-) 18 was not fully understood. This study was designed to evaluate the specific mechanism of NAC regulating IL-18. Materials and Methods. A total of 112 COPD patients and 103 health individuals were recruited in the study. Cytokine level in patients’ serum was measured by enzyme-linked immunosorbent assay (ELISA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…CS-induced lung inflammation can be attenuated by using ethanol extract from T. farfara flower buds through mediating the NLRP3 inflammasome, NF-κB and Nrf2 pathways [90]. N-Acetylcysteine has shown the potential to improve the immune state of COPD patients and a COPD animal model by downregulating pro-inflammatory and inflammatory cytokines, including IL-1β, IFN-γ, TNF-α and IL-18, through modulating and suppressing the NLRP3 inflammasome pathways of macrophages [91]. Magnesium isoglycyrrhizinate (MgIG), glycyrrhizic acid, is an anti-inflammatory agent originally used for treating hepatitis.…”
Section: Polyphenols Treatment Via Inflammasome In a Cigarette Smokin...mentioning
confidence: 99%
“…CS-induced lung inflammation can be attenuated by using ethanol extract from T. farfara flower buds through mediating the NLRP3 inflammasome, NF-κB and Nrf2 pathways [90]. N-Acetylcysteine has shown the potential to improve the immune state of COPD patients and a COPD animal model by downregulating pro-inflammatory and inflammatory cytokines, including IL-1β, IFN-γ, TNF-α and IL-18, through modulating and suppressing the NLRP3 inflammasome pathways of macrophages [91]. Magnesium isoglycyrrhizinate (MgIG), glycyrrhizic acid, is an anti-inflammatory agent originally used for treating hepatitis.…”
Section: Polyphenols Treatment Via Inflammasome In a Cigarette Smokin...mentioning
confidence: 99%
“…N‐acetylcysteine (NAC) has antioxidant and anti‐inflammatory effects on COPD. Liu et al 68 have found that NAC can inhibit the expression of NLRP3 in macrophages (Figure 2 ) and reduce the production of IFN‐γ in NK cells through clinical trials. Therefore, NAC can effectively inhibit the synthesis and release of IL‐18.…”
Section: Nlrp3 and Copdmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%